Use of phytoremediated sediments dredged in maritime port as plant nursery growing media. (15th January 2017) - Mattei, Paola; D'Acqui, Luigi P.; Nicese, Francesco P.; Lazzerini, Giulio; Masciandaro, Grazia; Macci, Cristina; Doni, Serena; Sarteschi, Francesco; Giagnoni, Laura; Renella, Giancarlo
Abstract: We evaluated the potential of a phytoremediated sediment (TR) dredged from maritime port as peat-free growth substrate for seven ornamental plants, in comparison with an untreated sediment (NT), in a greenhouse experiment. The studied plants were Quercus ilex, Photinia x fraseri, Viburnum tinus, Cistus albidus, Raphiolepis indica, Westringia fruticosa and Teucrium fruticans . Plant growth was monitored for ten months, and the changes in the physico-chemical properties, toxicity, microbial biomass and enzyme activities involved in the C, P and N cycles were also monitored during the plant growth period. The results showed that the studied ornamental plants could grow on both NT and TR sediments, but that the growth was higher on TR sediment. The plant growth induced changes in the sediment chemical functional groups, with clear separation between NT and TR sediments for each of the studied plant. Microbial biomass and enzyme activities significantly increased during the plant growth, more in TR than in NT sediment. Toxicity was detected in NT sediments during the plant growth whereas it was not observed in NT sediments during the whole growth period. We concluded that phytoremediation converted the dredged maritime sediments into suitable substrates for growing ornamental plants, and that the re-use by plant nursery industry can be a sustainable management and valorization for remediated sediments. Graphical abstract: Highlights: Untreated and phytoremediated marine sediment was tested to grow ornamental plants. Plants modified main chemical properties of sediments during growth. Biochemical activity was higher in phytoremediated than untreated sediments. Untreated but not phytoremediated sediments showed toxicity during plant growth.